What is the role of the next generation of cognitive robotics?. (2nd January 2022) - Shimoda, Shingo; Jamone, Lorenzo; Ognibene, Dimitri; Nagai, Takayuki; Sciutti, Alessandra; Costa-Garcia, Alvaro; Oseki, Yohei; Taniguchi, Tadahiro
Abstract : Social demand for robots to be our partners in daily life has been rapidly increasing. Cognitive robotics should play a major role in making robots our partners. To discuss the role of cognitive robotics, we organized the round table in December 2020. This review paper aimed at clarifying the role of cognitive robotics summarizing the discussion in the round table. The round table noted that the existence of uncertainty in the continuous control loop is a source of the need for cognitive robots and is the key factor that distinguishes cognitive robotics from the cognitive system in other fields. This paper summarized the discussion focusing on the creation of several cognitive functions without stopping even if the robots face novel uncertainty in daily life. We discussed information generalization, active sensing, prediction, and language communication as the necessary functions for future cognitive robots. One of the conclusions of the discussion is the importance of setting primitive but concrete targets for cognitive robotics research as cognitive robotics problems. We should continue to discuss the setting of these targets as a grand challenge for cognitive robotics. GRAPHICAL ABSTRACT: UF0001